Education Learning Strategies for Combating Stunting in Serdang Village, South Bangka Regency - Herdiyanti Herdiyanti (AIBPM Publisher, 2022)
This social study examines strategies for addressing stunting in Serdang Village, South Bangka Regency. The research employs a descriptive qualitative research method. Serdang Village has experienced a high prevalence of stunting in the past two years, with a slight decrease in recent years. The research findings indicate that the Serdang Village community has actively participated in various awareness-raising activities related to stunting, especially among pregnant and breastfeeding mothers. These activities are conducted by various stakeholders involved in addressing this social issue.